Immunogenic epitope scanning in bacteriolytic enzymes Pal and Cpl-1 and engineering Pal to escape antibody responses - Harhala, Marek Adam; Gembara, Katarzyna; Rybicka, Izabela; Kaźmierczak, Zuzanna Maria; Miernikiewicz, Paulina; Majewska, Joanna Marta; Budziar, Wiktoria; Nasulewicz-Goldeman, Anna; Nelson, Daniel C.; Owczarek, Barbara; Dąbrowska, Krystyna (Frontiers in Immunology, 2023)
Bacteriolytic enzymes are promising antibacterial agents, but they can cause a typical immune response in vivo. In this study, we used a targeted modification method for two antibacterial endolysins, Pal and Cpl-1. We identified the key immunogenic amino acids, and designed and tested new, bacteriolytic variants with altered immunogenicity. One new variant of Pal (257-259 MKS → TFG) demonstrated decreased immunogenicity while a similar mutant (257-259 MKS → TFK) demonstrated increased immunogenicity. A third variant (280-282 DKP → GGA) demonstrated significantly increased antibacterial activity and it was not cross-neutralized by antibodies induced by the wild-type enzyme. We propose this variant as a new engineered endolysin with increased antibacterial activity that is capable of escaping cross-neutralization by antibodies induced by wildtype Pal. We show that efficient antibacterial enzymes that avoid cross-neutralization by IgG can be developed by epitope scanning, in silico design, and substitutions of identified key amino acids with a high rate of success. Importantly, this universal approach can be applied to many proteins beyond endolysins and has the potential for design of numerous biological drugs.